Sonochemical reduction of carbon dioxide - Koblov, Alexander (Curtin University, 2011)
Emissions from the combustion of fossil fuels and cement production are responsible for approximately 75% of the increase of carbon dioxide (CO2) concentration in the atmosphere. 80% of the generated world energy is produced by burning fossil fuels (IPCC 2007) and such tendency is likely to remain unchanged in the nearest future. These number look more intimidating if consider the fact that in 2030, global energy demand was estimated to increase by 57% in comparison to 2004 (from 14.9 terrawatts (TW) in 2004 to 23.4 TW in 2030; International Energy Outlook 2007). Moreover, only 45% of CO2, released due to human activity since 1959, is absorbed by the nature (plants and the ocean) (IPCC 2007). Thus, the other 55% of CO2 from human activity remains in the atmosphere undeniably causing serious changes in the Earth‟s climate.With the potential impact of climate changes there is a considerable motivation to find solutions for reducing greenhouse gas emissions, particularly CO2. Moreover, the development of alternative energy sources is a commercially important task considering the fact that fossil fuels are non-renewable resources and will eventually deplete. It is well known that CO2 is a cheap and abundant source of carbon. Thus, the conversion of CO2 into fuels can be considered as a prospective method providing the possibility of CO2 recycling and as a result the decrease of CO2 concentrations in the atmosphere. Thus, over the past decades an increasing amount of global research efforts has focused on developing a CO2 utilization system. However, because CO2 is a very stable molecule, a large amount of energy is required to initiate its reduction. So the invention of an economically feasible method is the primary task in development of a CO2 reduction technology. The vast majority of work in this direction devoted to:- the application of new catalysts for CO2 reduction processes,- the use of various semiconductor technologies to harness solar energy as the energy input to the reaction of CO2 reduction, and- the development of bio-inspired processes in order to amplify the photosynthesis process in living organisms or create the artificial photosynthesisAn area of investigation that has received less attention is that of sonochemical reduction of CO2, or the use of ultrasound irradiation to reduce CO2 to basic fuel stock components. The chemical effect of ultrasound comes from acoustic cavitation phenomena – the formation, growth and collapse of cavitation bubbles. The collapse of cavitation bubbles results in generation of micro-zones of extremely high temperature (over 5000 K) and pressures (300 bar) (Nolting, and Nepparis 1950) which is the driving force for sonochemical reactions. Molecules trapped in cavitation bubbles undergo processes of radicalization and recombination due to the great amount of energy generated during the cavitation collapse.This thesis is devoted to experimental investigation of chemical utilization of CO2 using ultrasound as a source of energy. Sonochemical reduction of CO2 in various sonicating media is carried out in a wide range of experimental conditions. The main idea behind the experimental work performed is to investigate the ways of CO2 utilization into useable chemicals by its direct sonolysis or recombination of it with H2 while using the ultrasound (vibrational) energy, provided by the 20 kHz ultrasonic probe system. The study on sonochemical fixation of dense-phase and supercritical CO2 is also conducted. The efficiency and prospective usage of ultrasonic energy in the process of CO2 reduction is estimated based on the experimental results obtained. Additional study of the ultrasound-assisted oxidative desulfurization process of sulphur containing compounds by potassium permanganate (KMnO4) is conducted in order to investigate the effect of ultrasound on oxidation processes.